Ditch rotation irrigation coupled with multi-scale ecological reservoir operation - Linhui Mu; Tao Bai; Dong Liu; Hongwei Ji; Mingjiang Deng; LiangPeng Hong (Agricultural Water Management)
Aiming at the extensive ecological irrigation in arid regions, based on the theory of ditch rotation irrigation (DRI), this paper proposes a regulation method of water resources by coupling reservoir operation and Ditch rotation irrigation. Water demand of vegetation is met through combination of water saving and water supply, so that the ecosystem is adjusted to a new equilibrium state, to promote the coordinated development of aquatic ecology. Firstly, the DRI theoretical system is systematically expounded. Then, by establishing a coupling model of DRI and reservoir operation, the optimal operating scheme is proposed. Finally, the minimum limited water level suitable for DRI is proposed by irrigation effect. Results indicate that (1) DRI created a planar water delivery effect in the core area of riverbank vegetation, with a maximum irrigation area of 0.97 million m2 and water use efficiency of 84.9 %, to improve irrigation effect. (2) Through DRI implementation, the groundwater level in the experimental area rose by 0–0.97 m, and the vegetation coverage increased year by year. It indicates that the DRI improved the ecosystem's adapted ability under extreme drought conditions. (3) Through regulation method of water resources, the minimum limited water levels of reservoir before DRI were proposed, to provide sufficient ecological water for DRI in different periods. The research results have important theoretical value and practical significance for guiding the ecological protection and restoration of vegetation in riverbank.